Proteomic and phosphoproteomic analyses reveal extensive phosphorylation of regulatory proteins in developing rice anthers. (10th October 2015) - Ye, Juanying; Zhang, Zaibao; Long, Haifei; Zhang, Zhimin; Hong, Yue; Zhang, Xumin; You, Chenjiang; Liang, Wanqi; Ma, Hong; Lu, Pingli
Summary Anther development, particularly around the time of meiosis, is extremely crucial for plant sexual reproduction. Meanwhile, cell‐to‐cell communication between somatic (especial tapetum) cells and meiocytes are important for both somatic anther development and meiosis. To investigate possible molecular mechanisms modulating protein activities during anther development, we applied high‐resolution mass spectrometry‐based proteomic and phosphoproteomic analyses for developing rice (Oryza sativa) anthers around the time of meiosis (RAM). In total, we identified 4984 proteins and 3203 phosphoproteins with 8973 unique phosphorylation sites (p‐sites). Among those detected here, 1544 phosphoproteins are currently absent in the Plant Protein Phosphorylation DataBase (P3DB), substantially enriching plant phosphorylation information. Mapman enrichment analysis showed that 'DNA repair', 'transcription regulation' and 'signaling' related proteins were overrepresented in the phosphorylated proteins. Ten genetically identified rice meiotic proteins were detected to be phosphorylated at a total of 25 p‐sites; moreover more than 400 meiotically expressed proteins were revealed to be phosphorylated and their phosphorylation sites were precisely assigned. 163 putative secretory proteins, possibly functioning in cell‐to‐cell communication, are also phosphorylated. Furthermore, we showed that DNA synthesis, RNA splicing and RNA‐directed DNA methylation pathways are extensively affected by phosphorylation. In addition, our data support 46 kinase‐substrate pairs predicted by the rice Kinase‐Protein Interaction Map, with SnRK1 substrates highly enriched. Taken together, our data revealed extensive protein phosphorylation during anther development, suggesting an important post‐translational modification affecting protein activity.